Defining the goal of a data tax - Amanda Parsons (European Law Open)
Academics and policymakers alike have identified data taxes as a possible response to the emergence of the data economy. This essay aims to distill the two possible goals of a data tax. A data tax could serve as a Pigouvian tax, reducing data collection and the accompanying harms of datafication. Alternately, a data tax could serve as a new tax base, allowing for more effective revenue-raising and redistribution of the economic value being created in the data economy and preventing the concentration of economic power in the hands of digital companies. Which of these two is the primary goal of a data tax not only informs important design choices but also illuminates critical issues surrounding the political economic response to datafication. Therefore, advocates of data taxes must first consider the underlying goal of a data tax before calling for specific reforms.